Quality control of ethyl alcohol products used in sterilization spread in the local market - حكيم, رولا; محمد هارون , (Latakia University Journal -Medical Sciences Series, 2023)
As a result of the escalation of concerns about covid-19, there has been an increased demand for the use of disinfectants, especially ethyl alcohol solutions, as an aid in controlling infection and limiting the spread of the virus, which has led to the spread of many uncontrolled alcoholic preparations.. This study aims to control the quality of some ethyl alcohol preparations used for sterilization available in the Syrian market and to determine their ethyl alcohol content to ensure that it conforms to the declared concentration and its compliance with CDC recommendations (above 60%) using UV-Visible spectrophotometer at 595nm after forming a colorful complex with the Potassium dichromate agent. The qualitative and quantitative detection of methanol, which is a toxic and carcinogenic compound, in alcoholic preparations was performed, where the FDA recommended that the level of methanol in these preparations should not exceed 630 ppm, using UV-Visible spectrophotometer at 575 nm after forming a colorful complex with the chromotropic acid. 14 alcoholic preparations available in pharmacies were studied, 3 different batches of each product, were studied (42 samples of ethyl alcohol preparations available in the local market were studied). It was noted that 57% of the tested commercial samples were not according to CDC recommendations(ethanol concentration <60%) while 43% of the tested sterilizers were in compliance with CDC recommendations. The results of the analysis of alcoholic samples showed the presence of methanol in 27 (9 x 3) alcoholic preparations, out of 42 (14 x 3) preparations. 42.9% of the tested commercial samples were not according to FDA recommendations( methanol level >630 ppm) while 57.1% of the sterilizers tested were in compliance with FDA recommendation..